2020
DOI: 10.1002/celc.202000596
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Cobalt Iron Tetrathiomolybdate Coated on Cobalt Iron Carbonate Hydroxide Hydrate Nanowire Arrays for Overall Water Splitting

Abstract: Electrochemical water splitting is regarded as an ideal strategy for producing hydrogen energy. However, the ability to design efficient and durable noble-metal-free catalysts for decreasing the overpotential in the electrolysis process is in high demand.Here, it is demonstrated that cobalt iron carbonate hydroxide hydrate nanowire arrays on Ti mesh (CFOC/TM) obtained through a surface anion interchange method can lead to amorphous cobalt iron tetrathiomolybdate coated on crystalline cobalt iron carbonate hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Similarly, in NiFe LDH systems, the incorporation of iron and its percentage affected the OER activity, as studied by Trotochaud et al, who found that 25% of iron with nickel showed high OER activity . Hence, it will be indeed interesting to try different combinations of carbonate hydroxides with different molar ratios for enhancing the OER activity in different pH conditions. In addition, several other reports highlighted the use of transition-metal-based carbonate hydroxides as effective catalysts for OER and total water splitting applications. …”
Section: Introductionmentioning
confidence: 98%
“…Similarly, in NiFe LDH systems, the incorporation of iron and its percentage affected the OER activity, as studied by Trotochaud et al, who found that 25% of iron with nickel showed high OER activity . Hence, it will be indeed interesting to try different combinations of carbonate hydroxides with different molar ratios for enhancing the OER activity in different pH conditions. In addition, several other reports highlighted the use of transition-metal-based carbonate hydroxides as effective catalysts for OER and total water splitting applications. …”
Section: Introductionmentioning
confidence: 98%
“…There are various modulation strategies for improving the OER kinetics and decreasing the overpotential of MTMCHs for alkaline OER. [ 55–57,68,72–99 ] Table 1 summarizes the different approaches undertaken to achieve excellent OER performance with the good long‐term stability of MTMCHs.…”
Section: Mtmch Electrocatalysts In Oxygen Evolution Reactionmentioning
confidence: 99%
“…Reproduced with permission. [ 95 ] Copyright 2020, Wiley‐VCH GmbH. d) Schematic illustration of the formation of Cu 3 N@CoNiCHs@CF and e) TEM image of Cu 3 N@CoNiCHs showing the core–shell structure.…”
Section: Mtmch Electrocatalysts In Oxygen Evolution Reactionmentioning
confidence: 99%
See 2 more Smart Citations